2007
DOI: 10.1016/j.cmet.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Nampt/PBEF/Visfatin Regulates Insulin Secretion in β Cells as a Systemic NAD Biosynthetic Enzyme

Abstract: Intracellular nicotinamide phosphoribosyltransferase (iNampt) is an essential enzyme in the NAD biosynthetic pathway. An extracellular form of this protein (eNampt) has been reported to act as a cytokine named PBEF or an insulin-mimetic hormone named visfatin, but its physiological relevance remains controversial. Here we show that eNampt does not exert insulin-mimetic effects in vitro or in vivo but rather exhibits robust NAD biosynthetic activity. Haplodeficiency and chemical inhibition of Nampt cause defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

45
918
14
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 817 publications
(990 citation statements)
references
References 40 publications
45
918
14
13
Order By: Relevance
“…Although the PBEF protein lacks a classic signal sequence for secretion, it is constitutively released and detected in conditioned medium from many cell types (12,13,(33)(34)(35)(36)(37). PBEF is detectable in serum and synovial fluid (1,6), and the levels of PBEF have been found to be increased in patients with rheumatoid arthritis, in whom it is clinically correlated with the Disease Activity Score in 28 joints and elevated C-reactive protein level (1,2,6).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the PBEF protein lacks a classic signal sequence for secretion, it is constitutively released and detected in conditioned medium from many cell types (12,13,(33)(34)(35)(36)(37). PBEF is detectable in serum and synovial fluid (1,6), and the levels of PBEF have been found to be increased in patients with rheumatoid arthritis, in whom it is clinically correlated with the Disease Activity Score in 28 joints and elevated C-reactive protein level (1,2,6).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, exogenous PBEF is also described as an adipocytokine (referred to as visfatin), and can regulate cellular processes via activation of transcriptional events through NF-B, phosphatidylinositol 3-kinase, and MAP kinase (6-8). Several groups have shown that PBEF interacts with the insulin receptor (8-10); however, this notion remains controversial (11,12), and it may be that PBEF signals through an alternative signaling route. It is also unlikely that this signaling effect is attributable to the endotoxin that may be present in PBEF preparations, since coincubation with polymixin B shows no abrogation of PBEF signaling (6,10,13).…”
mentioning
confidence: 99%
See 3 more Smart Citations